2013
DOI: 10.1080/00140139.2012.751456
|View full text |Cite
|
Sign up to set email alerts
|

Do we need sustainability as a new approach in human factors and ergonomics?

Abstract: The increasing profile of sustainability on the international stage presents new opportunities for human factors/ergonomics. Positioning of the sustainability paradigm within human factors/ergonomics is discussed. Approaches to incorporating sustainability in the design of work systems are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…Designing sustainable work systems is one part of this (Zink and Fischer 2013). Similar results to those reported here regarding fatigue and recovery (Rose et al 1992) have also recently been used to address workers' capabilities and restrictions in manufacturing environments that need to be considered when designing for sustainable jobs (Jaber and Neumann 2010;Jaber, Givi, and Neumann 2013).…”
Section: Discussion On Some Methodological Aspectssupporting
confidence: 78%
“…Designing sustainable work systems is one part of this (Zink and Fischer 2013). Similar results to those reported here regarding fatigue and recovery (Rose et al 1992) have also recently been used to address workers' capabilities and restrictions in manufacturing environments that need to be considered when designing for sustainable jobs (Jaber and Neumann 2010;Jaber, Givi, and Neumann 2013).…”
Section: Discussion On Some Methodological Aspectssupporting
confidence: 78%
“…By linking more transparent reporting around the OHS agenda with brand image and organizational reputation (Hunter & Van Wassenhove, 2011), managers may leverage the differentiation strategy of the firm and shape new or boost existing marketing advantages while increasing customer loyalty (Neumann et al, 2014;Randall, 2005). Hence, OHS reporting may encapsulate an untapped reservoir of added value for the firm and attending the issue in a manner similar to promoting 'green' products or environmentally benign behaviour can contribute to the sustainability (reporting) agenda, primarily in terms of employee-management and consumer-company dialogue and fruitful engagement (Bolis, Brunoro, & Sznelwar, 2014;Mason & Simmons, 2011;Zink & Fischer, 2013). Nevertheless, recent evidence suggests that consumers do not receive adequate information on the working conditions of firms (Dixon et al, 2017), a problem which should be alarming to top management executives in terms of underlying inefficiencies and the potential scepticism or mistrust around OHS performance that mere 'aspirational talks' may spawn (Behm & Schneller, 2011;Boiral, 2013;Christensen, Morsing, & Thyssen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Statements above indicate both ergonomics and sustainable development are human centered and concerned with the joint optimization of the elements of complex socio-technical systems (Legg and Brown, 2010;Zink, 2014), implying that ergonomics could play an important role in assisting the transition to sustainable development (Moray, 1995;Dekker et al, 2013;Martin et al, 2013;Zink and Fischer, 2013;Bolis et al, 2014). Even though a few case studies on how ergonomics can help in achieving transition to sustainability have been reported (Wise, 2001;Rodriguez, 2004;Legg and Brown, 2010;Miller et al, 2012;Ryan and Wilson, 2013), a recent literature review conducted by Martin et al (2013) reported that only seven articles on ergonomics, design and sustainability were in ergonomics journals and thus there is a lack of clear published contributions from ergonomics to sustainable development, showing still very weak sign of ergonomists tacking sustainability issues.…”
Section: Introductionmentioning
confidence: 97%
“…Since the demands in dealing with the issues related to sustainable development are increasing (IISD, 2013) and the goals of ergonomics and sustainable development are somewhat congruent, integrating ergonomics into the field of sustainable development might offer promising solutions to solve sustainability related problems (Moray, 1995;Ryan and Wilson, 2013;Zink and Fischer, 2013) and open a window of opportunity for the discipline of ergonomics to devote attention to global problems (Haslam and Waterson, 2013;Martin et al, 2013). A number of efforts have been initiated in recent years to call for ergonomics to become more involved with sustainability.…”
Section: Introductionmentioning
confidence: 98%